2013
DOI: 10.4236/ars.2013.23025
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Applications: Beyond Land-Use and Land-Cover Change

Abstract: Remotely sensed (RS) imagery is increasingly being adopted in investigations and applications outside of traditional land-use land-cover change (LUCC) studies. This is due to the increased awareness by governments, NGOs and Industry that earth observation data provide important and useful spatial and temporal information that can be used to make better decisions, design policies and address problems that range in scale from local to global. Additionally, citizens are increasingly adopting spatial analysis into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Satellite remote sensing is an excellent tool to assess land ecosystem dynamics as it provides periodic, spatially explicit and consistent measurements of biophysical processes at the Earth's surface (Baynard 2013). It has become an established monitoring instrument in the fields of forestry (Achard et al 2002), agriculture (Atzberger 2013) and plant ecology (Xie et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite remote sensing is an excellent tool to assess land ecosystem dynamics as it provides periodic, spatially explicit and consistent measurements of biophysical processes at the Earth's surface (Baynard 2013). It has become an established monitoring instrument in the fields of forestry (Achard et al 2002), agriculture (Atzberger 2013) and plant ecology (Xie et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is suggested that a higher value of spatial and spectral detail is appropriate in the case that the classified object is smaller than the spatial resolution of satellite image [35,36]. Therefore, values of spectral and spatial detail were set to 18 for all imagery (possible range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The size of objects is defined by the parameter of minimum segment size, which merges segments smaller than this criterion with their best fitting neighboring segment.…”
Section: Segmentationmentioning
confidence: 99%
“…For better environmental analysis and making sound decisions, reliable information about the land-use/cover is vital (Basanna and Wodeyar, 2013;Tilahun and Teferi, 2015;Rawat and Kumar, 2015;El-Hattab, 2016).The Remote Sensing technique is a very advanced method and has great role for obtaining timely and valid information about land cover status (Fu, 2003;Manandhar et al, 2009;Blaschke, 2010;Subhash, 2012;Fichera et al, 2012;Forkuo and Frimpong, 2012;Baynard, 2013;Esmail et al, 2016;Haque and Basak, 2017;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%